TEENAGE BULLYING (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article analyzes the issue of adolescent delinquency. It examines delinquent behavior that occurs during adolescence, its causes, social and psychological factors, as well as its consequences. The article explores the family, school, and societal environments influencing adolescents' delinquent actions. Additionally, recommendations for preventing and combating adolescent delinquency are provided.